Processing Banana Waste Using the Continuous Flow Bin Vermicomposting Method at PT Nusantara Segar Abadi in Jembrana Bali - Faqih, Fajar Khun; Apriadi Aviantara, I Gusti Ngurah; Yulianti, Ni Luh (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
PT Nusantara Segar Abadi is a company that focuses on the cultivation of Cavendish bananas located in Jembrana Regency. According to the Central Statistics Agency, banana production data in Indonesia reached 9,245,427 tons in 2022, with PT NSA contributing 68,254 tons to the production in the same year. The challenge faced by PT NSA is t he improper handling of banana waste, which can lead to pollution and aesthetic issues. This research aims to create compost from banana waste using the continuous flow bin vermicomposting method. The research treatments include 7 kg of cow dung bedding wi th 1 kg of worms (A1), 7 kg of cow dung bedding with 1.5 kg of worms (A2), and 7 kg of cow dung bedding with 2 kg of worms (A3), each receiving 1.25 kg of banana waste every 3 days. Observations are conducted according to the Indonesian National Standard 1 9 - 7030 - 2004. The obtained data are analyzed using descriptive statistical analysis. After 18 days, the composting performance and characteristics of the compost vary. In terms of the C/N ratio parameter, treatment A1 exceeds the maximum standard at 20.12%, while treatment A2 is at 16.43%, and treatment A3 is at 16.11%, meeting the standard. Other characteristics include a pH value of 7.4 - 7.5, moisture content of 8.8% – 9.69%, organic C content of 27.43% – 29.37%, total N content of 1.46% – 1.71%, phosphorus (P) c ontent of 0.15% – 0.25%, and potassium (K) content of 0.33% – 0.37%, all of which comply with the compost standards specified in SNI 19 - 7030 - 2004. Treatment A3, with 2 kg of worms, proves to be the best treatment as technical parameters and macroelement conten t in all tests meet the standards